Physiological adaptations to resistance exercise as a function of age - Phillips, Bethan E.; Williams, John P.; Greenhaff, Paul L.; Smith, Kenneth; Atherton, Philip J. (American Society for Clinical Investigation, 2017)
BACKGROUND. The impact of resistance exercise training (RE-T) across the life span is poorly defined.